Sistem Pakar Untuk Diagnosis Penyakit Mata - Reisa, Reppy; Jusak, Jusak; Sudarmaningtyas, Pantjawati (Jurnal JSIKA, 2013)
Eyes are included as one of important human sense which is very useful human vision. But people usually take care the health of the eyes carelessly and it is also because of the less information for people to keep the healthy eyes. Besides the minimum health facilities for eyes in the hospitals and the clinics and also less expert that make this symptom cannot be handled rapidly. To help people, in this case the expert can use method of system with process of inference forward chaining. This system was created in website basic for spreading the information to people so the health of eyes can be handled quickly. Based on the research, four consumers and an expert the result : i) Throughout seven times of research in validity system the symptom can be detected,  ii) From the research of feature in system application the result are 3.4 from the consumer and 4.2 from the expert. From the result can be seen that this expert system application runs well, can be used and gives information of the symptoms and the solutions.